Effect of nitrogen partial pressure on the TCR of magnetron sputtered indium tin oxide thin films at high temperatures. Issue 9 (1st May 2022) - Liu, Zhichun; Liang, Junsheng; Zhou, Hao; Li, Jian; Yang, Mingjie; Cao, Sen; Xu, Jun
Abstract: Indium tin oxide (ITO) is a promising sensitive material for ultra-high temperature thin-film sensors ( UTTSs ) applied in thermal and mechanical parameters test in hot section parts. However, the instability of the temperature coefficient of resistance ( TCR ) in the ITO film is still one of the major limiting factors in accuracy improvement of the UTTSs . In this work, different ITO thin film samples were prepared by RF magnetron sputtering with various N2 /Ar ratios changing from 10%–40%, and the effect of nitrogen partial pressure ( NPP ) on the TCR of ITO films in elevated temperature from 500 °C to 1200 °C was studied. The micromorphology, crystallographic structures and electrical performances of ITO films were examined by scanning electron microscope ( SEM ), X-ray diffraction ( XRD ) and Hall effect measurement, respectively. Results show that lower crystallinity and smaller grain of ITO films can be observed with the increase of NPP . In addition, we found that the recrystallization is one of the main factors affecting the TCR repeatability in the thermal cycle test. The grain growth rate ( GGR ) is only 27.0% in the 20%N2 ITO film after the thermal cycle test from 500 °C to 1200 °C, far lower than that of the 40%N2 ITO film (309.6%). Consequently, the 20%N2 ITO film showed the lowest TCR volatility rates ( TVR ) after the thermal cycle test, which were respectively recorded as only about 0.5% and 2.1% at 800 °C and 1200 °C. The high TCR stability in the 20%N2 ITO film can be attributed to the formation of the stable phase structure during the thermal cycle test. Furthermore, the 20%N2 ITO film also has the smallest TCR compared with other ITO films.